Benzopyrene Serum Concentration After Endovenous Laser Ablation of the Great Saphenous Vein. (April 2013) - Klem, T.M.A.L.; Stok, M.; Grotenhuis, B.A.; Faber, M.J.; Leeuwen, S.P.J. van; Janssen, H.; Vrijland, W.W.
Background: During endovenous laser ablation (EVLA) of the great saphenous vein, patients often involuntarily mention an uncomfortable "burnt" smell and taste. When applying intense heat to proteins and carbohydrates, it is inevitable that polycyclic aromatic hydrocarbons (PAHs) are formed. This group of PAH includes the human carcinogen benzo[a]pyrene (B[a]P). This study determined the serum concentration of B[a]P just before and after EVLA. Methods: A total of 20 patients were included. The B[a]P serum concentration was determined just before and directly after EVLA. Results: In 18 patients, B[a]P was determined before and after EVLA. In 2 patients, EVLA was not possible. In this study, no elevated serum concentration of B[a]P was found before and after EVLA. Conclusion: It remains to be established which heat products cause the burnt smell and taste sensation in patients during EVLA. Further research is needed to determine whether EVLA can be considered as a safe procedure.